Risk factors associated with peritoneal carcinomatosis of gastric cancer in staging laparoscopy: A systematic review and meta-analysis - Guan, Guangmin; Li, Zhemin; Wang, Qi; Ying, Xiangji; Shan, Fei; Li, Ziyu (Frontiers in Oncology, 2022)
Background The optimal indications of staging laparoscopy in gastric cancer to detect peritoneal carcinomatosis are still controversial. We performed this systematic review and meta-analysis to quantify the relevance of the preoperative factors with peritoneal carcinomatosis to explore the indications of staging laparoscopy. Materials and methods Systematic searches were conducted using Medline, Embase, and the Cochrane Library in December 2021. On the basis of calculating the odds ratio (OR) of each factor, we quantified the association between the risk factors and peritoneal carcinomatosis such as clinical T/N stage, Borrmann type, and tumor markers, using meta-analysis with a random-effects model. Results A total of 21 case-control studies and one cohort study were obtained. T stage, N stage, and differentiation degree were most widely studied, with OR values of 2.96 (95% CI: 1.87–4.69), 1.22 (95% CI: 0.86–1.73), and 1.91 (95% CI: 1.42–2.56), respectively. Among all the factors, elevated CA125 (OR = 19.45, 95% CI: 4.71–80.30), Borrmann type IV (OR = 7.68, 95% CI: 3.62–16.27), and large tumor diameter (OR = 5.12, 95% CI: 2.55–10.31) had the highest OR. In particular, CA125 had the best predictability for peritoneal carcinomatosis but was only mentioned by three articles. Conclusions There was a cognitive gap between the awareness and importance of risk factors for peritoneal carcinomatosis. In addition to T4 stage, patients with factors with high OR, such as Borrmann type IV, large tumor diameter, and elevated CA125, should undergo staging laparoscopy.